Araceae endémicas del Perú - Lingán, Jorge (2006)
The Araceae are represented in Peru with 26 genera and nearly 250 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), most of them herbaceous epiphytes or hemiepiphytes. Here we recognize 52 endemic taxa in nine genera. One genus, Filarum, is endemic to Peru. Endemic aroids are found in Pluvial and Humid Montane Forests, and in the Humid Amazonian Forest, between 100 and 3000 m elevation. Thirteen endemic species have been registered within Peru’s protected areas network.